MAJULI RAAS MAHOTSAV AND ITS PRESENT-DAY RELEVANCE WITH RESPECT TO SOCIO-ECONOMIC DEVELOPMENT OF MAJULI - Tamuli, Padmaja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Majuli, the world’s largest river island (Guinness World Records) situated in the Brahmaputra River in Assam, India, hosts an annual cultural extravaganza in the month of November known as the Raas Mahotsav. This research article explores the historical and cultural significance of the Majuli Raas Mahotsav and analyses its present-day relevance in contributing to the socio-economic development of Majuli. For this study secondary data is collected through review of academic literature, from government reports, government websites and media articles. The study provides a comprehensive analysis of how the festival contributes to local economic growth, cultural preservation, and community cohesion. By examining the impact of the festival on tourism, local businesses, and community engagement, this study aims to shed light on the potential of cultural events like Majuli Raas Mahotsav as catalysts for regional development. This research contributes to the ongoing discourse on leveraging cultural heritage for sustainable development and offers valuable insights for policymakers, researchers, and cultural enthusiasts alike.